Principals' Managerial Skills in the Elementary Schools of Southern Papua - Werang, Basilius Redan; Wolomasi, Agustinus Kia; Wahyuni, Ni Putu (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2023)
This study aimed to describe teachers' perceptions of principals' managerial skills in the elementary schools of southern Papua, Indonesia. We used a survey research approach to explore the elementary school teachers' perceptions of school principals' managerial skills. To attain the objective, one survey questionnaire was distributed to 1277 respondents, conveniently picked from amongst the elementary school teachers in Southern Papua, Indonesia. All respondents were asked to give their perceptions on a four-point Likert scale by providing a checking mark (âˆš) on each given item that they value to be the most appropriate to describe the situation. The descriptive statistical analysis technique was performed by generating frequency and mean scores to describe teachers' perceptions of their school principals' managerial skills. The descriptive statistical analysis revealed that the elementary school principals' managerial skills were perceived as moderately low by the respondents as the general mean of the data is 2.6924E3 with a standard deviation of 174.34789 and a general mode of 2. Based on the result of descriptive statistical analysis, it is recommended that educational policymakers in Southern Papua to recruit school principal candidates based on the national standard required for a qualified school principal